SÁNCHEZ LÓPEZ, J. (2023). Superemocional: Una defensa del amor. Madrid: Continta Me Tienes - del Río Serantes, Abraham (Daimon Revista Internacional de Filosofia, 2026)
Reseña de SÁNCHEZ LÓPEZ, J. (2023). Superemocional: Una defensa del amor. Madrid: Continta Me Tienes